Cerebral processing of sharp mechanical pain measured with arterial spin labeling. Issue 1 (8th December 2021) - Cardinale, Vita; Demirakca, Traute; Gradinger, Tobias; Sack, Markus; Ruf, Matthias; Kleindienst, Nikolaus; Schmitz, Marius; Schmahl, Christian; Baumgärtner, Ulf; Ende, Gabriele
Abstract: Introduction: Arterial spin labeling (ASL) is a functional neuroimaging technique that has been frequently used to investigate acute pain states. A major advantage of ASL as opposed to blood‐oxygen‐level‐dependent functional neuroimaging is its applicability for low‐frequency designs. As such, ASL represents an interesting option for studies in which repeating an experimental event would reduce its ecological validity. Whereas most ASL pain studies so far have used thermal stimuli, to our knowledge, no ASL study so far has investigated pain responses to sharp mechanical pain. Methods: As a proof of concept, we investigated whether ASL has the sensitivity to detect brain activation within core areas of the nociceptive network in healthy controls following a single stimulation block based on 96 s of mechanical painful stimulation using a blunt blade. Results: We found significant increases in perfusion across many regions of the nociceptive network such as primary and secondary somatosensory cortices, premotor cortex, posterior insula, inferior parietal cortex, parietal operculum, temporal gyrus, temporo‐occipital lobe, putamen, and the cerebellum. Contrary to our hypothesis, we did not find any significant increase within ACC, thalamus, or PFC. Moreover, we were able to detect a significant positive correlation between pain intensity ratings and pain‐induced perfusion increase in the posterior insula. Conclusion: We demonstrate that ASL is suited to investigate acute pain in a single event paradigm, although to detect activation within some regions of the nociceptive network, the sensitivity of our paradigm seemed to be limited. Regarding the posterior insula, our paradigm was sensitive enough to detect a correlation between pain intensity ratings and pain‐induced perfusion increase. Previous experimental pain studies have proposed that intensity coding in this region may be restricted to thermal stimulation. Our result demonstrates that the posterior insula encodes intensity information for mechanical stimuli as well. Abstract : Using arterial spin labeling (ASL), one single block of sharp mechanical pain stimulation (96 s) induced perfusion increase in many areas of the nociceptive network. Moreover, a positive correlation between pain intensity ratings and perfusion increase in the posterior insula could be detected. Our results demonstrate that ASL constitutes a powerful alternative to BOLD fMRI for low‐frequency designs and that pain intensity coding in the posterior insula is not restricted to thermal stimulation.